Pengaruh Media Board Game Berbasis IT Terhadap Kemampuan Berpikir Simbolik Anak Usia 5-6 Tahun - Salsabila, Aisyah; Herman, Herman; Hasmawaty, Hasmawaty; Manga, Delvhina (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to determine the effect of using information technology-based board game media on the symbolic thinking skills of children aged 5-6 years at Mentari Kindergarten. This study uses a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The sample consisted of 20 children, who were divided into two groups: 10 children as the experimental group and 10 children as the control group. The experimental group was given treatment using IT-based board game media, while the control group used conventional media in the form of picture flashcards. Data collection techniques include observation, testing, and documentation. Data analysis was carried out using the Wilcoxon test with the help of SPSS version 23. The results of the study showed a significant increase in children's symbolic thinking skills in the experimental group with a Z value = -2.689 and p = 0.007 (p < 0.05), while the control group did not show a significant increase with p = 0.066 (p > 0.05). Thus, it can be concluded that IT-based board game media is effective in improving the symbolic thinking skills of early childhood